SAT0358 Pregnancy Outcomes Among Women with Chronic Inflammatory Arthritis or Psoriasis Treated and Not Treated with Etanercept (ENBREL) During Pregnancy. (9th June 2015) - Accortt, N.A.; Carman, W.J.; Enger, C.; Iles, J.; Anthony, M.S.
Abstract : Background: Limited population-based data are available regarding the safety of etanercept (ETN) use during pregnancy. Objectives: The purpose of this study was to describe the prevalence of pregnancy outcomes among women with chronic inflammatory arthritis (cIA) or psoriasis (PsO) with or without ETN exposure during pregnancy and among a non-disease, non-ETN control group. Methods: Using administrative claims data from 1995 through June 2012, we identified pregnant women with cIA (defined using ICD-9 codes as rheumatoid arthritis, juvenile idiopathic arthritis, psoriatic arthritis or ankylosing spondylitis) or PsO treated with ETN or not treated with any tumor necrosis factor inhibitor (TNFi) during pregnancy. A general population control group with no evidence of cIA or PsO and no TNFi treatment during pregnancy was frequency matched (5:1 ratio) to the ETN cIA or PsO groups for age and year of pregnancy. The prevalence of pregnancy outcomes (live birth, stillbirth, spontaneous abortion (SA), premature delivery) was calculated among 6 cohorts. A sample of medical charts was abstracted to verify the pregnancy outcome data identified by the claim. Results: We identified 4, 883 pregnancies leading to 3, 523 (72.1%) live births. There were 896 (18.3%) women with claims for miscarriages, ectopic pregnancies or spontaneous abortion, 433 (8.9%) with claims for non-spontaneous, therapeutic, elective, or unspecified (TEU) abortions and 45 (0.9%) with claims for stillbirths. The prevalence of these outcomes varied little between cohorts (Table ). The prevalence of premature delivery was similar among the cIA cohorts (exposed and unexposed) but higher than the general population. In our sample of 300 medical charts, outcome data were available for 236 (64 received charts had no pregnancy outcome data) and confirmed 98% of the live birth claims and 100% of the non-live birth claims. Conclusions: Pregnancy outcomes were comparable among cIA and PsO cohorts of women exposed to ETN or not exposed to any TNFi during pregnancy and general population controls. Acknowledgements: Study funded by Immunex, a wholly owned subsidiary of Amgen Inc. and through a research contract between Amgen, Inc and Optum, Epidemiology Disclosure of Interest: N. Accortt Shareholder of: Amgen, Employee of: Amgen, W. Carman Shareholder of: United Health Group, Employee of: Optum, C. Enger Shareholder of: United Health Group, Employee of: Optum, J. Iles Shareholder of: Amgen, Employee of: Amgen, M. Anthony Shareholder of: Amgen